Morphogenetic characterization of Xanthomonas citri pv. citri and its management - Ali, Subhan; Hameed, Akhtar; Binyamin, Rana; Alam, Muhammad Waqar; Aslam, Hafiz Muhammad Usman; Riaz, Hasan; Zaheer, Muhammad Saqlain (Elsevier, 2024)
Background: Pakistan 's economy largely depends on citrus cultivation, and citrus fruits generate significant foreign exchange. Xanthomonas citri pv. citri (Xcc) is the primary cause of citrus canker (CC), which poses a significant threat to the industry. The management of disease is made more difficult by the lack of resistant variants against different Xcc races. Understanding and addressing Xcc are critical for maintaining the industry given the economic reliance on citrus. Methods: In order to isolate Xcc in a lab, a thorough survey was conducted in the districts of Bahawalpur, Multan, and Dera Ghazi Khan to collect samples showing canker symptoms. Gram-negative bacteria were identified in the isolates by biochemical analysis, and Koch 's postulates confirmed Xcc as the CC causing agent. DNA extraction and sequencing were used in the molecular characterization, which confirmed the phylogenetic relationship with Xcc. Using the disc sensitivity method, nine antibiotics were tested at 300, 500, and 700 ppm concentrations to evaluate CC management. Amoxicillin was found to be highly effective in inhibiting the growth of Xcc colonies. Results: The study provided morphogenetic insights and established Xcc as the causal agent of CC. All strains matched Xcc in molecular characterization, but antibiotic sensitivity testing revealed inconsistent efficacy. Amoxicillin proved to be very effective at stopping the growth of Xcc colonies at every tested dosage. Conclusion: This study makes an important contribution to our understanding of XCC and helps the citrus industry develop better disease control plans. Future interventions against citrus canker can benefit greatly from the understanding provided by morphogenetic characterization and antibiotic sensitivity profiles. The discovery of amoxicillin 's high efficacy highlights the drug 's potential for treating diseases linked to Xcc. These results help to protect citrus growing, maintaining the viability of an important industry in Pakistan 's agricultural landscape.
Keywords: Antibiotics; Characterization; Citrus canker; Management; Xanthomonas citri pv. citri